Our Path: Empower Maine Women Network and Leadership - Chitam, Mufalo; Rohani, Parivash; de Does, Laura; Rostampour, Ghomri; Fasehun, Oyinloluwa; Smart, Bethany; Morrill, Jan (Maine Policy Review, 2018)
On March 24, 2018, the women of the Empower Network sat down to discuss the concept of leadership and their definition of what makes a leader. They were asked to reflect on the idea of empowerment and specifically tie empowerment to kindness, suffrage, and tolerance. This article excerpts their discussion and demonstrates how the Empower Network relates to their definition of leadership.